Employees' Emotional Intelligence, Motivation & Productivity, and Organizational Excellence A Future Trend in HRD - Chakrabarti, Gagari (Springer Singapore, 2018)
This book focuses on emotional intelligence, which has emerged as a factor in superior on-the-job performance and ability to lead an effective life. Based on an emerging country, namely India, the book deviates from traditional approaches by focusing on non-cognitive rather than cognitive skills to explain and predict performance and achievements. It finds that those with strong intrinsic non-cognitive skills, like trustworthiness, conscientiousness, adaptability, initiative and commitment have a better chance of becoming effective leaders with enhanced service-orientation, empathy and conflict management skills -traits desired by any organization striving for efficiency. It also demonstrates that while such imponderable, intrinsic skills matter, they cannot replace discernible psycho-social factors and hence, effective hiring strategies must focus on behavioural competence along with cognitive skills. The book also discusses organizations' desire to ensure a working environment that is vibrant and positive in an attempt to prevent unconstructive or disruptive factors and to ensure improved performances over time. The book is a valuable resource for corporate personnel, as well as for researchers and practitioners in the field.